2018
DOI: 10.1186/s12879-018-3454-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between HIV testing social norms and self-efficacy on HIV testing among Chinese men who have sex with men: results from an online cross-sectional study

Abstract: BackgroundIncreasing human immunodeficiency virus (HIV) testing is critical for HIV control. This study aimed to evaluate the interaction between social norms and self-efficacy on HIV testing among Chinese men who have sex with men (MSM).MethodsWe conducted an online survey in eight Chinese cities in Shandong and Guangdong Provinces in July 2016. We included participants who were born as a male, at least 16 years old, currently living in one of the designated cities, and had ever engaged in anal sex with a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Social norms are social attitudes of approval or disapproval that are specific to what should be or should not be done in the context of health. Perceived social norm supporting HIV testing was a facilitator for MSM to take up HIV testing ( 22 ). MSM may value the opinions of their male sex partners or peers.…”
Section: Introductionmentioning
confidence: 99%
“…Social norms are social attitudes of approval or disapproval that are specific to what should be or should not be done in the context of health. Perceived social norm supporting HIV testing was a facilitator for MSM to take up HIV testing ( 22 ). MSM may value the opinions of their male sex partners or peers.…”
Section: Introductionmentioning
confidence: 99%
“…The framing of reminder messages was categorized into (1) neutrally framed, (2) personalized, (3) positively framed, (4) negatively framed, and (5) social norms. The framing of messages was populated based on previous research on message framing in health communication (Camenga et al, 2014;Farrow et al, 2017;Kiene et al, 2005;Levin et al, 1998;Martin-Smith et al, 2018;Neuberger & Pabian, 2019;Perry et al, 2015;Yamin et al, 2019;Zhao et al, 2018).…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Although we know from behavioral economics that under many circumstances, message framing (i.e., what words are used) and the message medium (i.e., how it is delivered) can influence behavioral outcomes (Farrow et al, 2017;Levin et al, 1998;Martin-Smith et al, 2018;Neuberger & Pabian, 2019;Zhao et al, 2018), few studies have explored the effects of message framing in the sexual health field. These studies have found that message framing impacted sexual decisionmaking and risk behavior (Camenga et al, 2014;Garcia-Retamero & Galesic, 2010;Kiene et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“… Jang et al (2013) found that self-efficacy in resisting alcohol consumption moderated the effect of perceived descriptive drinking norm on both drinking intention and behavior such that the normative influences were stronger among those reporting a low level of refusal self-efficacy. Zhao et al (2018) revealed that self-efficacy in HIV testing moderated the effect of perceived social norm on HIV testing in the past 3 months and in lifetime such that self-efficacy enhanced the normative influence. Although Zhao et al (2018) did not specify the type of perceived social norm in their study, their measure of this variable is consistent with the conceptualization of perceived descriptive norm.…”
Section: Introductionmentioning
confidence: 96%
“… Zhao et al (2018) revealed that self-efficacy in HIV testing moderated the effect of perceived social norm on HIV testing in the past 3 months and in lifetime such that self-efficacy enhanced the normative influence. Although Zhao et al (2018) did not specify the type of perceived social norm in their study, their measure of this variable is consistent with the conceptualization of perceived descriptive norm. Therefore, similar to research suggesting that perceived injunctive norm enhanced the effect of perceived descriptive norm on the target behavior ( Lee et al, 2007 ; Göckeritz et al, 2010 ; Pandon et al, 2016 ), these studies also suggest that individuals may not follow perceived descriptive norms blindly.…”
Section: Introductionmentioning
confidence: 96%